The Impact of Online Teaching on Chinese Postgraduates’ Attitudes Toward Second Language Acquisition in Australia During COVID-19: Insights for Sports Psychology and Cross Cultural Adaptation - Xiaoou Fu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The COVID-19 pandemic has triggered rapid changes in educational practices worldwide, significantly influencing teaching methods and learning experiences across diverse contexts. This study investigates the impact of online teaching on Chinese postgraduate students’ attitudes toward second language acquisition (SLA) during the pandemic, with particular focus on psychological adaptability and cross-cultural challenges. Using a quantitative approach, data was collected through an online survey that assessed students' attitudes toward online teaching, its efficiency, and the relationship between online teaching and SLA. The study involved 43 Chinese postgraduate students (aged 23–25, native Chinese speakers) at the University of Queensland, Australia. Data analysis revealed that most students demonstrated positive attitudes toward online teaching, acknowledging its role in facilitating SLA during challenging times. However, the findings also highlighted potential complexities and psychological challenges posed by online teaching, particularly in terms of maintaining engagement and motivation in a cross cultural learning environment. These insights have implications for sports psychology, particularly in understanding the psychological resilience and adaptability required for success in remote and cross-cultural settings. By addressing the challenges of online education, educators can better support students’ cognitive and emotional needs, fostering not only language acquisition but also skills relevant to teamwork, communication, and psychological well being in global and sports-related contexts.